1990
DOI: 10.1063/1.857610
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the boundary conditions for a Hele–Shaw bubble

Abstract: Effective boundary conditions are derived to be used with the classical Hele–Shaw equations in calculating the shape and motion of a Hele–Shaw bubble. The main assumptions of this analysis are that the displaced fluid wets the plates, and that the capillary number Ca and the ratio of gap width to characteristic bubble length ε are both small. In a small region at the sides of the bubble, it is found that the thin-film thickness scales with ε2/5 Ca4/5, rather than the Ca2/3 scaling that is valid over most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
48
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 9 publications
4
48
0
Order By: Relevance
“…There is moreover an additional term which is the above mentioned O( 2 ) correction that comes from the interface curvature in the (x, y) plane, expressed here in dimensional form. Further generalisation has been discussed by other authors such as [9][10][11] who considered a confined bubble in a Hele-Shaw type situation. When the (x, y) plane interface slope is not small, it has been shown that the additional term is indeed the in-plane interface curvature multiplied by π/4 [9][10][11].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…There is moreover an additional term which is the above mentioned O( 2 ) correction that comes from the interface curvature in the (x, y) plane, expressed here in dimensional form. Further generalisation has been discussed by other authors such as [9][10][11] who considered a confined bubble in a Hele-Shaw type situation. When the (x, y) plane interface slope is not small, it has been shown that the additional term is indeed the in-plane interface curvature multiplied by π/4 [9][10][11].…”
Section: Introductionmentioning
confidence: 94%
“…Further generalisation has been discussed by other authors such as [9][10][11] who considered a confined bubble in a Hele-Shaw type situation. When the (x, y) plane interface slope is not small, it has been shown that the additional term is indeed the in-plane interface curvature multiplied by π/4 [9][10][11]. Moreover, in the case where the interface displacements are not locally perpendicular to the interface one should consider the normal velocity U n of the air-liquid interface so that a normal capillary number Ca n = µU n /γ must be used instead of Ca in (1) [9][10][11].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The small thickness assumption allows a lubrication approximation transforming the 3D boundary value problem in a 2D one while the small wavelength approximation allows an average on larger length-scales. An asymptotic analysis adapted from [12] shows that the function yðxÞ describing the drop shape satisfies a two-dimensional Laplace law modified by the radiation pressure along the normal. It is a Riccati equation:…”
mentioning
confidence: 99%